2019
DOI: 10.3390/rs11202406
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Patterns in Vegetation Growth-Limiting Factors over Europe

Abstract: Water and energy are recognized as the most influential climatic vegetation growth-limiting factors. These factors are usually measured from ground meteorological stations. However, since both vary in space, time, and scale, they can be assessed by satellite-derived biophysical indicators. Energy, represented by land surface temperature (LST), is assumed to resemble air temperature; and water availability, related to precipitation, is represented by the normalized difference vegetation index (NDVI). It is hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
3
21
0
2
Order By: Relevance
“…Because evapotranspiration cools the earth's surface, rising surface temperatures may be linked to decreasing water content or a soil moisture deficit and thus water stress in the vegetation canopy [52,53]. If both variables are well correlated, the limiting factor for vegetation growth can be determined depending on the season and location: The NDVI-LST correlation is negative if water is the limiting factor, but it is positive if energy is the limiting factor [36,54,55].…”
Section: Correlation Analysis Between Ndvi and Lstmentioning
confidence: 99%
See 1 more Smart Citation
“…Because evapotranspiration cools the earth's surface, rising surface temperatures may be linked to decreasing water content or a soil moisture deficit and thus water stress in the vegetation canopy [52,53]. If both variables are well correlated, the limiting factor for vegetation growth can be determined depending on the season and location: The NDVI-LST correlation is negative if water is the limiting factor, but it is positive if energy is the limiting factor [36,54,55].…”
Section: Correlation Analysis Between Ndvi and Lstmentioning
confidence: 99%
“…Finally, approaches also exist within this topic to determine areas and time periods where water is the primary limiting factor for plant growth. In Europe, a correlation analysis between LST and NDVI has revealed that energy was a limiting factor mainly in northern Europe, at high altitudes, and in spring, while water limited plant growth mainly in southern Europe and in summer [36].…”
Section: Introductionmentioning
confidence: 99%
“…Energy-limited regimes merge gradually into water-limited regimes from Scandinavia southwards to the Mediterranean in Europe (Teuling et al, 2009). Karnieli et al (2019) investigated the relationship of the NDVI and land surface temperature at European scale, hypothesizing that a positive relationship indicates an energy-limited condition and a negative one a waterlimited condition. Our results are mostly in agreement with the findings of their study that temperature and the NDVI are comprehensively negatively related in summer in Mediterranean Europe, whereas in spring this is only the case at the southernmost regions of Mediterranean Europe, while in other areas either neutral or negative relationships prevail.…”
Section: Interpretation Of Temporal and Spatial Patterns In The Meditmentioning
confidence: 99%
“…Nilai NDVI dan SPL dianalisis sebelum mengkaji sebaran nilai UTFVI karena beberapa alasan. Pertama, NDVI menggambarkan distribusi spasial tutupan vegetasi di daerah penelitian dan secara statistik berkorelasi dengan SPL (Karnieli et al, 2019). Kedua, SPL merupakan nilai yang mendasari sebaran UTFVI di lokasi tertentu.…”
Section: ………………………………………(3)unclassified
“…Namun demikian, jika nilai NDVI jauh di bawah nol maka cenderungnya akan merepresentasikan tubuh air (Jensen, 2015). Pada dasarnya, nilai SPL memiliki hubungan berbanding terbalik dengan nilai NDVI yang berarti bahwa semakin tinggi nilai SPL maka akan semakin rendah nilai NDVI (Karnieli et al, 2019) Namun, hal tersebut tidak sepenuhnya berlaku, terutama untuk objek tubuh air. Pada objek tubuh air, nilai NDVI-nya akan cenderung sangat rendah tetapi nilai SPL-nya akan cenderung rendah.…”
Section: Pembahasanunclassified